Optimizing Parcel Locker Locations in Minimarkets in Residential Areas Using the Incapacitated P-Median Model - Nur Umami Sukma Dewi Sofyan Putri; Sutanto; Nahry (Jurnal Syntax Transformation, 2026)
The rapid growth of e-commerce in Indonesia has increased the complexity and cost of last-mile delivery. Parcel lockers offer a potential solution to reduce distribution inefficiencies, such as increased vehicle travel distance, congestion, and emissions associated with home delivery, while also improving service quality through flexible parcel collection. This study develops an optimization model for parcel locker placement in residential areas by utilizing minimarkets as potential facility locations, using an incapacitated p-median approach. The model aims to minimize the total system cost, consisting of distribution costs and user access costs, with service quality represented by access distance. The analysis is conducted using 210 demand points across seven subdistricts in Tebet District, South Jakarta, with 44 minimarkets as candidate locations. Two scenarios are compared: without and with administrative boundary constraints. The results indicate that the unrestricted scenario provides better service quality, reflected in shorter access distances, along with lower system costs. In contrast, the restricted scenario leads to longer access distances and higher system costs. Quantitatively, the implementation of parcel lockers reduces total distribution travel distance by up to 70% compared to home delivery. These findings demonstrate that optimizing parcel locker locations can improve logistics system efficiency and support sustainable urban transport planning.